ABC Analysis Towards Drug Needs Planning in Pharmacy Installation of RSUD Kota Yogyakarta In 2010 - Heny Puspa Sari; Sulanto Saleh Danu; Endang Sulistyani (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2017)
Background: Consumption method is one of the standard methods which are used to plan the number of drugs need. This method provides good accuracy of the prediction toward the drug needs planning. However, this does not always provide satisfactory outcomes because this method cannot provide the outlook of the investment value toward each drug. To obtain a plan suitable to the need and purpose, drug planning can be analyzed using several methods; one of them is ABC analysis which is also known also as Pareto or Pareto Law 80/20, a method used in logistic management to classify goods into three based on the investment value, namely A with 75-80%, B with 15-20%, and C with 5-10%. Objective: To obtain the outlook about the process and the outcomes of the ABC analysis towards drug needs planning in Pharmacy Installation of RSUD Kota Yogyakarta in 2010. Methods: The data were collected by collecting and observing the secondary data in 2010, as well as carrying out some deep interviews to some related correspondences. Results: This research showed that the planning process is carried out by the Pharmacist in pharmacy supply sub-division and the correction carried out by the head of the hospital Pharmacy. Moreover, in the hospital there was no special planner team to plan the need of the drug, and there was no involvement from related parties. Drug item from group A has been prioritized. Conclusion: The planning that has been carried out so far was effective and efficient, as can be seen from the planning appropriateness with the highest occurring disease pattern in the hospital from each service unit.